Proteomics of Mycobacterium Infection: Moving towards a Better Understanding of Pathogen-Driven Immunomodulation - Hoffmann, Eik; Machelart, Arnaud; Song, Ok-Ryul; Brodin, Priscille (Frontiers in Immunology, 2018)
Intracellular bacteria are responsible for many infectious diseases in humans and have developed diverse mechanisms to interfere with host defense pathways. In particular, intracellular vacuoles are an essential niche used by pathogens to alter cellular and organelle functions, which facilitate replication and survival. Mycobacterium tuberculosis (Mtb), the pathogen causing tuberculosis in humans, is not only able to modulate its intraphagosomal fate by blocking phagosome maturation, but has also evolved strategies to successfully prevent clearance by immune cells and to establish long-term survival in the host. Mass spectrometry (MS)-based proteomics allows the identification and quantitative analysis of complex protein mixtures and is increasingly employed to investigate host-pathogen interactions. Major challenges are limited availability and purity of pathogen-containing compartments as well as the asymmetric ratio in protein abundance when comparing bacterial and host proteins during the infection. Recent advances in purification techniques and MS technology helped to overcome previous difficulties and enable the detailed proteomic characterization of infected host cells and their pathogen-containing vacuoles. Here, we summarize current findings of the proteomic analysis of Mycobacterium-infected host cells and highlight progress that has been made to study the protein composition of mycobacterial vacuoles. Current investigations focus on the pathogenicity during Mtb infection, which will allow to better understand pathogen-induced changes and immunomodulation of infected host cells. Consequently, future research in this field will have important implications on host response, pathogen survival and persistence, induced adaptive immunity and metabolic changes of immune cells promoting the development of novel host-directed therapies in tuberculosis.